System and method for intensifying degradation of biodegradable plastic compost through mild alkali heat pretreatment and application
Through mild alkaline heat pretreatment methods, the problem of slow degradation of biodegradable plastics in compost is solved, and its degradation and mineralization is accelerated under mild conditions, improving the reliability and safety of compost products, and reducing the risk of secondary pollution.
Patent Information
- Application Number
- CN202410260685.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-07
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-03-07
AI Technical Summary
Biodegradable plastics degrade slowly in compost, which may affect compost corruption and increase the risk of secondary pollution. The existing alkaline heat pretreatment methods require high temperature and high alkali concentration, which is costly and not suitable for simple and rapid enhancement of compost degradation performance.
The mild alkaline heat pretreatment method is adopted to accelerate its degradation in compost by performing alkaline heat treatment above the glass transition temperature of the biodegradable plastic.
Significantly accelerate the degradation and mineralization of biodegradable plastics under mild conditions, shorten the degradation time, improve the reliability and safety of compost products, reduce the adverse effects on compost corruption, and reduce the risk of secondary pollution.
Smart Images

Figure HDA0004730806080000011 
Figure HDA0004730806080000012 
Figure HDA0004730806080000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic solid waste treatment and disposal, and relates to a system, method and application of mild alkaline heat pretreatment to enhance biodegradable plastic composting degradation. Background Art
[0002] The "Opinions on Further Strengthening Plastic Pollution Control" points out that the production, sales and use of some plastic products such as non-degradable plastic bags should be banned in an orderly manner. The demand and application of biodegradable plastics as a substitute for traditional plastics are growing rapidly. The total output of biodegradable plastics in my country in 2022 is about 795,000 tons, and the main types are thermoplastic starch (TPS), polylactic acid (PLA), polybutylene adipate / terephthalate (PBAT), etc. Biodegradable plastic products are usually certified under controlled composting conditions, while actual composting often uses natural heating methods. Due to the complexity of the composting system and differences in material properties, biodegradable plastics may be difficult to degrade and have a lag period. The time to reach the standard degradation rate (≥90%) is far longer than the operating cycle of the composting system. In addition, biodegradable plastics may also affect the maturity of the compost, reduce the fertilizer efficiency of the compost, and cause secondary pollution.
[0003] Alkali-heat pretreatment is often used to enhance the anaerobic digestibility of biodegradable plastics. Under alkaline conditions, ester bonds of biodegradable plastics will hydrolyze, resulting in a decrease in molecular weight and the production of hydrophilic groups such as hydroxyl groups. When the temperature exceeds its glass transition temperature, the molecular chain will unfold, accelerating the hydrolysis process. In addition, alkaline-heat pretreatment can increase the surface area and porosity of the plastic through surface erosion, increasing bioaffinity. The combined effect of the above mechanisms can accelerate the degradation of biodegradable plastics. The current problems include: (1) The application scenarios currently proposed are mostly for single polymer particles in the form of granules or powders, rather than the more commonly used mixed biodegradable plastic products. (2) Although alkaline-heat pretreatment with higher temperatures (>100°C) and / or longer times (>1h) and / or higher alkali concentrations (>0.1mol / L) can dissolve more organic matter in biodegradable plastics into the liquid phase for subsequent anaerobic digestion, it is not suitable for simply and quickly enhancing the composting degradation performance of biodegradable plastics. In addition, liquid phase biological treatment with high alkali concentrations is more difficult. Therefore, it is necessary to find mild and effective alkaline-heat pretreatment conditions.
[0004] The patent document with publication number CN109593638A discloses a system and method for promoting the degradation and methanogenic utilization of polylactic acid plastic by hydrothermal pretreatment, including a material mixing unit, a crushing and impurity removal unit, a heat exchange device, a hydrothermal treatment reactor, an anaerobic fermentation reactor, a dehydration device and a biogas combustion system, as well as a method for water / alkali heat modification of polylactic acid plastic, which can shorten the degradation time from more than 100 days to less than 30 days. However, the pretreatment temperature in the invention is 120-200 ° C, which needs to be pressurized. In practical applications, a corresponding system is required, which is costly and only targets a single polylactic acid plastic. In actual biodegradable plastics, polybutylene adipate terephthalate (PBAT) is often mixed, which is considered to be difficult to degrade in anaerobic digestion. Therefore, this technology lacks universality. In addition, it is also worth exploring whether alkali heat pretreatment can enhance the degradation of biodegradable plastic compost, the optimal conditions for pretreatment, whether it can weaken its adverse effects on the composting system, and the control of secondary pollution. Summary of the invention
[0005] In order to solve the deficiencies in the prior art, the present invention provides a system, method and application for strengthening the composting degradation of biodegradable plastics by mild alkali-heat pretreatment, wherein mild alkali-heat pretreatment conditions are applied to biodegradable plastics, and under conditions above their glass transition temperature, their molecular chains are softened to promote non-biological hydrolysis of polymers, reduce their crystallinity and molecular weight, and improve their biological affinity, which is more conducive to the occurrence of subsequent microbial enzymolysis. The present invention focuses on strengthening the composting degradation performance of biodegradable plastics by mild alkali-heat pretreatment, rather than dissolving a large amount of organic matter under extreme conditions to promote anaerobic methanogenesis. The conditions are relatively mild, organic matter is less dissolved, time-consuming and cost-effective. The pretreated biodegradable plastics of the present invention are applied to controlled composting or natural composting, which can accelerate the degradation and mineralization of biodegradable plastics, reduce their adverse effects on compost maturity, reduce the risk of secondary pollution, and improve the reliability and safety of compost product applications, which has important environmental significance and economic benefits.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention proposes a system for strengthening the composting degradation of biodegradable plastics by mild alkali-heat pretreatment, comprising a plastic crushing unit, an alkali-heat treatment unit, a heat exchange unit, a solid-liquid separation unit, a liquid phase treatment unit, a material mixing unit and a composting unit; wherein the plastic crushing unit, the alkali-heat treatment unit, the solid-liquid separation unit, the material mixing unit and the composting unit are connected in sequence, and the biodegradable plastics are pretreated and then degraded by composting; the heat exchange unit is connected to the alkali-heat treatment unit and the solid-liquid separation unit for heat recycling, and is connected to the liquid phase treatment unit for treating the separated liquid phase.
[0008] The technical difficulty / technical difficulty overcome by the present invention lies in how to improve the degradation performance of biodegradable plastics through mild alkaline heat pretreatment under the conditions of controlling the organic matter dissolution ratio, time and cost, promote their degradation in the aerobic composting process, and reduce the environmental risks of residual microplastics and the adverse effects on the resource utilization of organic solid waste.
[0009] The present invention also proposes a method for strengthening the composting degradation of biodegradable plastics by mild alkaline heat pretreatment, the steps of which are as follows:
[0010] Step 1: crush the biodegradable plastic to reduce its size;
[0011] Step 2: pretreating the biodegradable plastic crushed in step 1 under mild alkaline and thermal conditions and performing solid-liquid separation;
[0012] Step 3: Degrading the biodegradable plastic pretreated in step 2 through controlled composting or natural composting.
[0013] In the present invention, the biodegradable plastic refers to a type of biodegradable plastic product that can ultimately degrade into carbon dioxide and / or methane, water and mineralized inorganic salts of the elements contained therein, and new biomass under various environmental conditions. The biodegradable plastic is made from one or more of polybutylene adipate / terephthalate (PBAT), polylactic acid (PLA), starch, inorganic fillers, etc. as raw materials, and complies with GB / T 41010-2021 "Degradability Performance and Labeling Requirements for Biodegradable Plastics and Products"; the crushing and alkali-heat pretreatment method is used to enhance the composting degradation performance of biodegradable plastics, and the pretreated biodegradable plastic is used for controlled composting and / or natural composting.
[0014] In step 1, the biodegradable plastic is crushed by mechanical crushing such as rotary cutting, shredding, or other suitable methods, and the area of the biodegradable plastic after crushing is 1 to 100 cm 2 ; preferably 1 to 25 cm 2 More preferably, 1 to 4 cm 2 .
[0015] In step 2, the pretreatment temperature is controlled at 60-100°C, preferably 100°C.
[0016] In step 2, the pretreatment is carried out under normal pressure.
[0017] In step 2, the base includes one or more of NaOH, KOH, Ca(OH)2, etc.; preferably NaOH.
[0018] In step 2, the concentration of the base is 0-0.1 mol / L in terms of NaOH, preferably 0.1 mol / L.
[0019] In step 2, the pretreatment time is 10 to 60 minutes, preferably 40 minutes.
[0020] In step 2, solid-liquid separation is performed by plate and frame filter pressing, centrifugation or suction filtration, and the liquid phase component is recovered to preheat the alkali solution to achieve heat recovery.
[0021] In step 2, the ratio of the mass of the biodegradable plastic to the volume of the alkali solution is 1:1 to 1:10, preferably 1:10, in units of g / mL.
[0022] In step 2, the biodegradable plastic is hydrolyzed after alkaline heat pretreatment. After the hydrolysis is completed, the pH value of the liquid phase component is 7.0-12.5, the concentration of total organic carbon dissolved from the biodegradable plastic is 0.1-3 g / L, and the mass of total organic carbon dissolved from the biodegradable plastic is within 5% of the original mass of total organic carbon.
[0023] In step 2, the water contact angle of the solid phase component after alkali-heat pretreatment, i.e. the biodegradable plastic after pretreatment, is reduced by 5% to 25%, and the molecular weight is reduced by 3% to 30%.
[0024] In step three, the controlled composting is carried out for 30 to 60 days at a temperature of 50 to 60° C., and the material ratio is 1 g of biodegradable plastic: (20 to 100) g of compost matrix; preferably, the controlled composting is carried out for 60 days at a temperature of 58° C., and the material ratio is 1 g of the biodegradable plastic: 100 g of compost matrix; the mineralization rate of the biodegradable plastic after alkali-heat pretreatment is 80% to 90%, and the molecular weight is reduced by 40% to 60%.
[0025] In step three, the natural composting is carried out for 30 to 40 days, the temperature range is 25 to 70° C., and the material ratio is 1 g of biodegradable plastic: (10 to 150) g of compost matrix; preferably, the natural composting is carried out for 40 days, the temperature range is 40 to 70° C., and the material ratio is 1 g of the biodegradable plastic: 150 g of compost matrix; the mineralization rate of the biodegradable plastic after alkali-heat pretreatment is 60% to 80%, and the molecular weight is reduced by 50% to 60%; the compost seed germination index reaches more than 85%.
[0026] The present invention also proposes the use of the system as described above, or the method as described above in the alkali-thermal pretreatment and / or composting degradation of biodegradable plastics.
[0027] Compared with the prior art, the beneficial effects of the present invention include: aiming at the problem that biodegradable plastics degrade slowly in aerobic composting and may be unfavorable for composting maturity, the present invention proposes a simple and rapid mild alkali heat pretreatment method, which, when applied to mixed biodegradable plastic products, can reduce the molecular weight by 3% to 30% and the water contact angle by 5% to 25% after 10 to 60 minutes of pretreatment, thereby improving the composting degradation performance; the reaction temperature does not exceed 100°C, the conditions are mild, the process can be carried out under normal pressure, the time is relatively short, the mass of the dissolved total organic carbon accounts for less than 5% of the original total organic carbon mass, which is lower than 10% to 90% in the prior art, the organic matter loss is small, and the subsequent composting degradation will not be affected. The pretreated biodegradable plastic can be applied to controlled composting to accelerate degradation and mineralization. After 30 to 60 days of controlled composting according to the method of the present invention, the mineralization rate of the biodegradable plastic can reach 80% to 90%, and the molecular weight is reduced by 40% to 60%, while the mineralization rate in the prior art is 40% to 70%, and the molecular weight is only reduced by 30% to 40%. The application of the biodegradable plastic to natural composting can reduce plastic residues and reduce the adverse effects of the biodegradable plastic on the compost, so that the compost can better meet the standards of maturity and harmlessness. After 30 to 40 days of natural composting according to the method of the present invention, the mineralization rate of the biodegradable plastic is 60% to 80%, the molecular weight is reduced by 50% to 60%, and the compost seed germination index reaches more than 85%, while in the prior art, the mineralization rate of the biodegradable plastic is 30% to 50%, the molecular weight is reduced by 30% to 40%, and the seed germination index is about 70%. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0029] Figure 1 It is a system schematic diagram of the present invention.
[0030] Figure 2 The invention discloses a liquid component pH, total organic carbon and terephthalic acid concentration of the biodegradable plastic after low-concentration alkali heat pretreatment.
[0031] Figure 3 It is the molecular weight change of the biodegradable plastic of the present invention after low-concentration alkali heat pretreatment.
[0032] Figure 4 The invention discloses a liquid component pH, total organic carbon and terephthalic acid concentration of the biodegradable plastic after alkali-heat pretreatment for different time periods.
[0033] Figure 5The invention discloses a liquid component pH, total organic carbon and terephthalic acid concentration of the biodegradable plastic after alkali-heat pretreatment.
[0034] Figure 6 The invention discloses the surface microstructure and water contact angle of the biodegradable plastic after pretreatment.
[0035] Figure 7 It is the change of molecular weight of the biodegradable plastic after pretreatment of the present invention.
[0036] Figure 8 It is the appearance change of the biodegradable plastic of the present invention after controlled composting.
[0037] Fig. 9 This is the residual condition of the biodegradable plastic of the present invention after natural composting.
[0038] Fig.10 It is the change of molecular weight of the biodegradable plastic of the present invention after natural composting.
[0039] Fig.11 The invention relates to the change in thermal properties of the biodegradable plastic after natural composting.
[0040] Fig.12 The biodegradable plastic of the present invention undergoes natural composting changes.
[0041] Fig.13 It is the change of the seed germination index of the biodegradable plastic after natural composting of the present invention. DETAILED DESCRIPTION
[0042] The present invention is further described in detail with reference to the following specific examples and drawings. The process, conditions, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art and are not particularly limited by the present invention.
[0043] Obviously, the described embodiments are only some embodiments of the present invention, rather than all embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0045] Unless otherwise specified, the test materials used in the examples are all conventional biochemical reagents.
[0046] The present invention provides a system and method for enhancing the composting degradation of biodegradable plastics by mild alkaline heat pretreatment, which belongs to the field of organic solid waste treatment and disposal. The system schematic diagram of the present invention is shown in Figure 1 The steps are as follows: crush the biodegradable plastic to reduce the size; pre-treat and separate the solid and liquid under mild alkaline and hot conditions; and perform controlled composting or natural composting. The method provided by the present invention can simply and quickly enhance the composting degradation performance of biodegradable plastics; when applied to controlled composting, it can accelerate the degradation and mineralization of biodegradable plastics; when applied to natural composting, it can reduce plastic residues and reduce the adverse effects of biodegradable plastics on composting, so that the compost can better meet the standards of maturity and harmlessness.
[0047] Example 1 Low-concentration alkali heat pretreatment of mixed biodegradable plastic products
[0048] Reduce the area of common mixed biodegradable plastic products in the form of films made of PBAT, PLA, starch and inorganic fillers to 1-4 cm 2 , mixed with alkaline solution at a ratio of 1:10 (unit: g / mL), alkaline heat pretreatment was performed under constant temperature and pressure, solid-liquid separation was performed by suction filtration, and the liquid phase component was recovered to preheat the alkaline solution to achieve heat recovery. The 60°C, 40min, 0.01mol / LNaOH condition group was recorded as BDP-2, the 80°C, 20min, 0.01mol / LNaOH condition group was recorded as BDP-4, and the 100°C, 60min, 0.01mol / LNaOH condition group was recorded as BDP-9.
[0049] like Figure 2 As shown, after alkali-heat pretreatment, the pH of the liquid components of BDP-2 and BDP-9 decreased to 11.7, while the pH of the liquid component of BDP-9 decreased to 9.8. Therefore, BDP-9 was more fully hydrolyzed than the other two groups, indicating that high temperature and long time conditions are more conducive to the hydrolysis of biodegradable plastics. The total organic carbon concentration of BDP-9 was also the highest, at 674 mg / L. Since the hydrolysis of the PBAT component produces terephthalic acid monomers, the concentration of terephthalic acid can also reflect the degree of hydrolysis. BDP-9 has the highest concentration, at 79 mg / L.
[0050] like Figure 3 As shown in the figure, after alkali-heat pretreatment, the number average molecular weight (Mn) and weight average molecular weight (Mw) of each group decreased by 1% to 3% and 3% to 12% with BDP-2, BDP-4, and BDP-9, respectively, indicating that the biodegradable plastics underwent initial hydrolysis, which was more conducive to subsequent biodegradation. The polymer dispersibility index PDI (Mw / Mn) decreased significantly, with BDP-9 decreasing the most from 2.26 to 2.06, indicating that both macromolecules and small molecules were hydrolyzed during the degradation process, and the molecular weight distribution tended to be concentrated and uniform.
[0051] Therefore, the ratio of biodegradable plastic to alkaline solution is 1:10 (in g / mL), the pretreatment temperature is 100°C, the pressure is normal, the alkali concentration is 0.01 mol / L in terms of NaOH, and the treatment time is 60 min, which is more conducive to the hydrolysis of the mixed biodegradable plastic product.
[0052] Example 2 Alkali-heat pretreatment of mixed biodegradable plastic products at different times
[0053] The same biodegradable plastic was subjected to alkali-heat pretreatment according to the alkali-heat pretreatment method of Example 1 of the present invention, at 100° C. and 0.1 mol / L NaOH, with other conditions being the same, and the pretreatment was performed for 10, 20, 40, 60, 90, and 120 min, respectively.
[0054] like Figure 4 As shown in the figure, with the increase of alkali heat pretreatment time, the pH value showed a downward trend, from 12.5 to 10.0, indicating that the biodegradable plastic was continuously hydrolyzed; the total organic carbon concentration and terephthalic acid concentration of the liquid phase component showed an upward trend, and the growth was more obvious within 10 to 40 minutes, and then the growth slowed down, which was related to the preferential hydrolysis of the amorphous region of the biodegradable plastic, indicating that the pretreatment time did not need to be too long. Therefore, the optimal pretreatment conditions for the mixed biodegradable plastic product were a ratio of 1:10 (in g / mL), a pretreatment temperature of 100°C, normal pressure, an alkali concentration of 0.1 mol / L in terms of NaOH, and a treatment time of 40 minutes.
[0055] Example 3 Mild alkaline heat pretreatment of mixed biodegradable plastic products
[0056] The same biodegradable plastic was subjected to alkali-heat pretreatment according to the alkali-heat pretreatment method of Example 1 of the present invention. The 80°C, 40 min, 0.1 mol / LNaOH condition group was recorded as BDP-5, the 100°C, 20 min, 0.1 mol / LNaOH condition group was recorded as BDP-7, the 100°C, 40 min, 0.1 mol / LNaOH condition group was recorded as BDP-10, and the control group without pretreatment was recorded as BDP.
[0057] like Figure 5 As shown, the pH of the liquid component after alkali-heat pretreatment was 12.0-12.5, the total organic carbon concentration of BDP-10 was the highest, which was 2731 mg / L, and the dissolved total organic carbon mass was within 5% of the original total organic carbon mass. Among them, the PBAT component was hydrolyzed to produce terephthalic acid monomer, and the BDP-10 concentration was the highest, which was 408 mg / L. The results showed that the BDP-10 group was most fully hydrolyzed within the reasonable range of organic matter dissolution, and the pretreatment effect was the best.
[0058] like Figure 6As shown in the figure, after alkali-heat pretreatment, a large number of pore structures appeared on the surface of the biodegradable plastic bag, and the surface roughness and surface area increased significantly, which was more conducive to the attachment of microorganisms. The water contact angle decreased by 8% to 22% compared with the initial BDP-5, BDP-7, and BDP-10, and the plastic surface changed from hydrophobic to hydrophilic, which was more conducive to hydrolysis and biodegradation.
[0059] like Figure 7 As shown, after alkali-heat pretreatment, the Mn and Mw of the biodegradable plastics decreased by 4% to 16% and 13% to 26% with BDP-5, BDP-7, and BDP-10, respectively. The PDI of BDP-9 decreased the most, from 2.26 to 1.99, and the molecular weight distribution tended to be concentrated and uniform.
[0060] Therefore, according to the above results, the optimal pretreatment conditions for the mixed biodegradable plastic products are that the ratio of biodegradable plastic to alkaline solution is 1:10 (in g / mL), the pretreatment temperature is 100°C, the normal pressure, the alkali concentration is 0.1 mol / L in terms of NaOH, and the treatment time is 40 min.
[0061] Example 4 Controlled composting of biodegradable plastics after mild alkaline heat pretreatment
[0062] The same biodegradable plastic was subjected to alkali-heat pretreatment according to the alkali-heat pretreatment method of Example 1 of the present invention. The group setting was the same as that of Example 3 of the present invention. Controlled composting was performed using activated vermiculite prepared from mature compost under controlled conditions at 50°C. The material ratio was 1g biodegradable plastic: 25g pumice: 50g activated vermiculite. Sampling, turning and supplementing mature compost inoculum (1mL / 10g activated vermiculite) were performed every 7 days to maintain microbial activity. Figure 8 As shown, traces of microbial attachment appeared on the surface of biodegradable plastics after 7 days. The optimal pretreatment condition group was BDP-10, that is, the ratio of biodegradable plastic to alkaline solution was 1:10, the unit was g / mL, the pretreatment temperature was 100°C, the normal pressure, the alkali concentration was 0.1 mol / L in terms of NaOH, the treatment time was 40 min, and obvious damage appeared on the surface; after 60 days, the mineralization rate of BDP-10 in the optimal pretreatment condition group reached 90%, which was 100% higher than that of the control group, and the mineralization rates of other treatment groups also exceeded 60%. Under the optimal pretreatment conditions, the degradation rate of 90% or more was achieved within 180 days as stipulated in the arbitration standard for biodegradable plastics, and the time was shortened by one third.
[0063] Example 5 Natural composting of biodegradable plastics after mild alkaline heat pretreatment
[0064] The same biodegradable plastic was subjected to alkali-heat pretreatment according to the alkali-heat pretreatment method of Example 1 of the present invention, and the conditions were the same as those of the optimal treatment group BDP-10, i.e., the ratio of biodegradable plastic to alkali solution was 1:10 (in g / mL), the pretreatment temperature was 100°C, the pressure was normal, the alkali concentration was 0.1 mol / L in terms of NaOH, and the treatment time was 40 min. After the pretreatment, the biodegradable plastic was mixed with organic solid wastes such as kitchen waste and straw for natural composting, and the material ratio was 1 g biodegradable plastic: 25 g straw: 100 g kitchen waste. A pretreatment group (TF) was set, and a control group (NF) without pretreatment and a blank group (CK) without biodegradable plastic addition were also set. The compost was placed in a composting container for natural heating, and the temperature range was 25-70°C. The compost was turned every 3 days. After the composting was completed, the degradation of the biodegradable plastic and the maturity of the compost were analyzed.
[0065] like Fig. 9 As shown, after composting, the plastic residues in the TF group in the size ranges of 1-2mm, 2-5mm, and >5mm were lower than those in the NF group. Especially in the size range of >5mm, the plastic residues in the TF group were only 40% of those in the NF group, indicating that the biodegradable plastics were more degradable after pretreatment and the residual microplastics were less (by mass). Alkali-heat pretreatment promoted the degradation of biodegradable plastics during composting while reducing plastic residues, thereby improving the safety of compost products.
[0066] like Fig.10 As shown, after pretreatment, the molecular weight of the TF group decreased by 14.06% (Mn) and 11.69% (Mw) compared with the NF group. During the composting process, as the biodegradable plastics degraded, the Mn and Mw of each group generally showed a downward trend, and the decline was more obvious in the early stage of composting. At the end of composting, the molecular weight of the TF group was 14467g / mol (Mn) and 30744g / mol (Mw), which was 45% (Mn) and 42% (Mw) lower than that of the NF group, respectively. Since the decrease in Mn was slightly greater than that in Mw, the PDI of each group increased slightly compared with the initial value, indicating that the long molecular chains in the biodegradable plastics were broken during the degradation process, the long and short chains were mixed, and the molecular weight distribution became wider.
[0067] like Fig.11 As shown in the figure, due to the molecular weight reduction caused by hydrolysis after pretreatment, the initial decomposition temperature of the TF group (the temperature corresponding to the mass loss of 10%, denoted as T d ) and the maximum decomposition rate temperature (the temperature corresponding to the fastest thermal decomposition rate, denoted as T max ) were 8.68℃ and 4.24℃ lower than those of the NF group. d and T max As the easily degradable part of the compost degrades, the thermal stability of the remaining biodegradable plastics increases. d and Tmax The results showed that the degradation rate of TF group was higher than that of NF group, which indirectly reflected that the degradation rate of TF group was higher. In addition, the mass percentage of thermal decomposition residues in NF group was 24.35%, which was higher than that in NF group (22.46%), confirming the above results.
[0068] The ratio of fulvic acid to humic acid, i.e., the humic acid to fulvic acid ratio, can be used to judge the maturity of compost. The higher the humic acid to fulvic acid ratio, the higher the maturity. Fig.12 As shown, the Hufu ratio decreased slightly in the early stage of composting, and continued to increase after reaching the high temperature period. At the end of composting, the TF group was significantly higher than the NF group and slightly higher than the CK group, indicating that the addition of biodegradable plastics is not conducive to compost maturity, while pretreatment can reduce its adverse effects and promote the compost humification process.
[0069] Seed germination index is also an important indicator for evaluating compost maturity. Fig.13 As shown in the figure, at the end of composting, the GI of each group exceeded 70%, reaching the standard of organic fertilizer, indicating that the compost was mature. The TF group and the CK group were close, both exceeding 85%, significantly higher than the NF group, which was consistent with the Hu Fubi result, indicating that pretreatment can reduce the adverse effects of biodegradable plastic bags on compost maturity and improve the quality of compost products.
[0070] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0071] As used in the present invention, the term "comprising" is an open expression, that is, including the contents specified in the present invention but not excluding other contents.
[0072] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0073] The protection content of the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the present invention, changes and advantages that can be thought of by those skilled in the art are included in the present invention and are protected by the attached claims.
Claims
1. A system for enhancing the composting degradation of biodegradable plastics by mild alkaline heat pretreatment, characterized in that: The system includes a plastic crushing unit, an alkali heat treatment unit, a heat exchange unit, a solid-liquid separation unit, a liquid phase treatment unit, a material mixing unit and a composting unit; wherein the plastic crushing unit, the alkali heat treatment unit, the solid-liquid separation unit, the material mixing unit and the composting unit are connected in sequence, and the biodegradable plastic is pre-treated and then degraded by composting; the heat exchange unit is connected to the alkali heat treatment unit and the solid-liquid separation unit for heat recycling, and is connected to the liquid phase treatment unit for treating the separated liquid phase.
2. A method for enhancing the composting degradation of biodegradable plastics by mild alkaline heat pretreatment, characterized in that: The method comprises the following steps: Step 1: crush the biodegradable plastic to reduce its size; Step 2: pretreating the biodegradable plastic crushed in step 1 under mild alkaline and thermal conditions and performing solid-liquid separation; Step three: degrading the biodegradable plastic pretreated in step two through controlled composting or natural composting.
3. The method according to claim 2, characterized in that The biodegradable plastic refers to a type of biodegradable plastic product that can ultimately degrade into carbon dioxide and / or methane, water and mineralized inorganic salts of the elements it contains, and new biomass under various environmental conditions. It uses one or more of polybutylene adipate / terephthalate, polylactic acid, starch, and inorganic fillers as raw materials and complies with GB / T 41010-2021 "Degradation Performance and Labeling Requirements for Biodegradable Plastics and Products".
4. The method according to claim 2, characterized in that: In the step 1, the biodegradable plastic is crushed by mechanical crushing such as rotary cutting, shredding and pulverizing, and the area of the biodegradable plastic after crushing is 1 to 100 cm 2 .
5. The method according to claim 2, characterized in that: In the step 2, the pretreatment temperature is controlled at 60-100°C; the pretreatment is carried out at normal pressure; the alkali is selected from one or more of NaOH, KOH, and Ca(OH)2; the alkali concentration in the alkali solution is 0-0.1 mol / L in terms of NaOH; the pretreatment time is 10-60 min; and the solid-liquid separation is carried out by plate and frame filter pressing, centrifugation or suction filtration.
6. The method according to claim 2, characterized in that In the step 2, the ratio of the mass of the biodegradable plastic to the volume of the alkali solution is 1:1 to 1:10, in units of g / mL.
7. The method according to claim 2, characterized in that In the step 2, the biodegradable plastic is hydrolyzed after alkaline heat pretreatment, and the pH of the liquid component after the hydrolysis is completed is 7.0-12.5, the concentration of total organic carbon dissolved from the biodegradable plastic is 0.1-3 g / L, and the mass of organic carbon dissolved from the biodegradable plastic is within 5% of the original total organic carbon mass.
8. The method according to claim 2, characterized in that: After the biodegradable plastic is pretreated with alkali heat, the water contact angle is reduced by 5% to 25%, and the molecular weight is reduced by 3% to 30%.
9. The method according to claim 2, characterized in that: In the step 3, the controlled composting is carried out for 30 to 60 days at a temperature range of 50 to 60° C., and the material ratio is 1 g of the biodegradable plastic: (20 to 100) g of composting matrix; the mineralization rate of the biodegradable plastic after alkali-heat pretreatment is 80% to 90%, and the molecular weight is reduced by 40% to 60%; And / or, the natural composting is carried out for 30 to 40 days at a temperature range of 25 to 70° C., the material ratio is 1 g of the biodegradable plastic: (10 to 150) g of compost matrix, the mineralization rate of the biodegradable plastic after alkali-heat pretreatment is 60% to 80%, the molecular weight is reduced by 50% to 60%, and the compost seed germination index reaches more than 85%.
10. Use of the system according to claim 1 or the method according to any one of claims 2 to 9 in the alkali-thermal pretreatment and composting degradation of biodegradable plastics.
Citation Information
Patent Citations
Compost method for kitchen waste and organic fertilizer prepared by kitchen waste
CN108585980A
System and method for hydrothermal pretreatment to promote polylactic acid plastic degradation and methanation utilization
CN109593638A
Microbial complex microbial inoculant for enhancing degradation of biodegradable plastic compost as well as preparation method and application of microbial complex microbial inoculant
CN118165852A
Method for efficiently degrading sludge containing large amount of microplastics through sodium hydroxide hydrothermal pretreatment
CN119797709A
Process for preparing plastics self-degradable in compost environment
CN1304954A